Mind the Gap: Current Treatment Alternatives for GERD Patients Failing Medical Treatment and Not Ready for a Fundoplication. Issue 2 (16th April 2021) - Huynh, Phuong; Konda, Vani; Sanguansataya, Suchakree; Ward, Marc A.; Leeds, Steven G.
Abstract : Background: Gastroesophageal reflux disease is associated with Barrett esophagus, esophageal adenocarcinoma, and significantly impacts quality of life. Medical management is the first line therapy with surgical fundoplication as an alternative therapy. However, a small portion of patients who fail medical therapy are referred for surgical consultation. This creates a "gap" in therapy for those patients dissatisfied with medical therapy but are not getting referred for surgical consultation. Three procedures have been designed to address these patients. These include radiofrequency ablation (RFA) of the lower esophageal sphincter, transoral incisionless fundoplication (TIF), and magnetic sphincter augmentation. Materials and Methods: A Pubmed literature review was conducted of all publications for RFA, TIF, and MSA. Four most common endpoints for the 3 procedures were compared at different intervals of follow-up. These include percent of patients off proton pump inhibitors (PPIs), GERD-HRQL score, DeMeester score, and percent of time with pH <4. A second query was performed for patients treated with PPI and fundoplications to match the same 4 endpoints as a control. Results: Variable freedom from PPI was reported at 1 year for RFA with a weighted mean of 62%, TIF with a weighted mean of 61%, MSA with a weighted mean of 85%, and fundoplications with a weighted mean of 84%. All procedures including PPIs improved quality-of-life scores but were not equal. Fundoplication had the best improvement followed by MSA, TIF, RFA, and PPI, respectively. DeMeester scores are variable after all procedures and PPIs. All MSA studies showed normalization of pH, whereas only 4 of 17 RFA studies and 3 of 11 TIF studies reported normalization of pH. Conclusions: Our literature review compares 3 rival procedures to treat "gap" patients for gastroesophageal reflux disease with 4 common endpoints. Magnetic sphincter augmentation appears to have the most reproducible and linear outcomes but is the most invasive of the 3 procedures. MSA outcomes most closely mirrors that of fundoplication.